1997
DOI: 10.1117/12.275705
|View full text |Cite
|
Sign up to set email alerts
|

<title>Study of shell interior noise control</title>

Abstract: There is a growing interest in the application of smart materials technology to the aircraft interior noise control problem. Some outstanding issues with the interior noise control problem include development of sensory systems that can lead to global sound level reduction in the cabin, and the safety concern of structural actuators used to reduce noise radiation. This paper presents two comparative studies: 1) comparison of several sensor configurations by using acoustic microphones, and 2) comparison of stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19] Acoustic energy density, defined as the sum of the acoustic potential and kinetic energy densities at a point, is commonly estimated using the two-microphone method 1 and is given by ͑see the Appendix͒…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Acoustic energy density, defined as the sum of the acoustic potential and kinetic energy densities at a point, is commonly estimated using the two-microphone method 1 and is given by ͑see the Appendix͒…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several authors have found energy density to be an effective sensor for active noise control applications, as it measures the total energy at a point, and generally outperforms microphones. [2][3][4][5][6] In the past, estimation of acoustic energy density has been made using one of two methods: time domain experiments or noise-free frequency domain simulations. The time domain method involves the use of additional electronics ͑either analog or digital͒ to calculate the pressure average and the particle velocity between the two sensing elements.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several authors have found energy density to be an effective sensor for active noise control applications, as it measures the total energy at a point, and generally outperforms microphones. [2][3][4][5][6] The bias errors arising from the inherent and instrumentation errors in energy density sensing have been thoroughly investigated. [7][8][9] Additionally, the estimation of potential energy density and kinetic energy density in the frequency domain and the associated statistical errors have been discussed by Elko.…”
Section: Introductionmentioning
confidence: 99%